2016
DOI: 10.14336/ad.2016.0117
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Endoplasmic Reticulum Stress is Involved in the Neuroprotective Effect of bFGF in the 6-OHDA-Induced Parkinson’s Disease Model

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disorder with complicated pathophysiologic mechanisms. Endoplasmic reticulum (ER) stress appears to play a critical role in the progression of PD. We demonstrated that basic fibroblast growth factor (bFGF), as a neurotropic factor, inhibited ER stress-induced neuronal cell apoptosis and that 6-hydroxydopamine (6-OHDA)-induced ER stress was involved in the progression of PD in rats. bFGF administration improved motor function recovery, increased tyrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 50 publications
1
20
0
1
Order By: Relevance
“…Additionally, endoplasmic reticulum (ER) stress seems to play a critical role in the progression of Parkinson’s disease. Results obtained by Cai et al [ 79 ] indicate that ER stress-induced apoptosis in PD might be inhibited by a basic fibroblast growth factor (bFGF). Administration of bFGF improved motor function recovery, increased tyrosine hydroxylase positive neuron survival, and upregulated the levels of neurotransmitters in the brain of a rat model of Parkinson’s disease.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, endoplasmic reticulum (ER) stress seems to play a critical role in the progression of Parkinson’s disease. Results obtained by Cai et al [ 79 ] indicate that ER stress-induced apoptosis in PD might be inhibited by a basic fibroblast growth factor (bFGF). Administration of bFGF improved motor function recovery, increased tyrosine hydroxylase positive neuron survival, and upregulated the levels of neurotransmitters in the brain of a rat model of Parkinson’s disease.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used as a therapeutic agent for the restoration and maintenance of neuronal function in both basic and clinical studies. Basic fibroblast growth factor (bFGF) is highly expressed in the nervous system and exerts multiple roles supporting the survival and growth of cultured neurons and neural stem cells [8][9][10]. Although bFGF and NGF have distinctive neuroprotective properties, their short half-life and rapid diffusion rate seriously hinders their clinical applicability.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress disrupts endoplasmic reticulum (ER) which is a key component of cellular protein homeostasis, controlling the regulation of protein trafficking, synthesis, folding, and degradation (Perri et al ., 2016 ). The implementing process in protein quality control in the ER is the unfolded protein response (UPR), which is activated upon ER stress to reestablish homeostasis through a sophisticated transcriptionally and translationally regulated signaling network (Hoozemans & Scheper, 2012 ; Cai et al ., 2016 ). Accumulation of misfolded proteins within the ER activates the UPR resulting in the execution of adaptive or non-adaptive signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, enormous efforts have been deployed to formulate new strategies that address neuronal degeneration. The latest studies indicated that mitochondrial dysfunction and ER-stress targeted regimens could be a potential approach to overcome neurodegeneration (Kondratyev et al ., 2007 ; Benyair et al ., 2011 ; Hoozemans & Scheper, 2012 ; Leitman et al ., 2013 ; Cai et al ., 2016 ; Ogen-Shtern et al ., 2016 ). Following this line of evidence, a few recent studies showed that some natural polyphenolic compounds exhibited neuroprotective effects by regulation of redox stress-mediated UPR response (Wu et al ., 2015 ; Cheng et al ., 2016 ).…”
Section: Introductionmentioning
confidence: 99%